2016
DOI: 10.3389/fpls.2016.00592
|View full text |Cite
|
Sign up to set email alerts
|

Clarification on Host Range of Didymella pinodes the Causal Agent of Pea Ascochyta Blight

Abstract: Didymella pinodes is the principal causal agent of ascochyta blight, one of the most important fungal diseases of pea (Pisum sativum) worldwide. Understanding its host specificity has crucial implications in epidemiology and management; however, this has not been clearly delineated yet. In this study we attempt to clarify the host range of D. pinodes and to compare it with that of other close Didymella spp. D. pinodes was very virulent on pea accessions, although differences in virulence were identified among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 58 publications
(89 reference statements)
2
34
0
Order By: Relevance
“…Previous studies have reported that the genus Didymella is widely distributed in field and ornamental crops, wild plants and most saprobes species are commonly found in living or dead aerial parts of herbaceous, wooden plants [8], and some act as mutualistic endophytes [34]. Didymella pinodes (formerly known Mycosphaerella pinodes) has been reported as the main causal agent of Ascochyta blight, which is one of the most important fungal diseases of the pea (Pisum sativum) worldwide [35,36]. D. tanaceti and D. rosea have been identified as plant pathogens that cause the tan spot in pyrethrum [30].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the genus Didymella is widely distributed in field and ornamental crops, wild plants and most saprobes species are commonly found in living or dead aerial parts of herbaceous, wooden plants [8], and some act as mutualistic endophytes [34]. Didymella pinodes (formerly known Mycosphaerella pinodes) has been reported as the main causal agent of Ascochyta blight, which is one of the most important fungal diseases of the pea (Pisum sativum) worldwide [35,36]. D. tanaceti and D. rosea have been identified as plant pathogens that cause the tan spot in pyrethrum [30].…”
Section: Discussionmentioning
confidence: 99%
“…These include brown to black lesions, spreading from the upper part of the main root into the root system and the stem; discoloration of the root system; and softening and decay of the root and lower stem cortex. (Aveskamp, de Gruyter, Woudenberg, Verkley, & Crous, 2010;Baćanović-Šišić, Šišić, Schmidt, & Finckh, 2017;Barilli, Cobos, & Rubiales, 2016;Haware, 1981;Tran, You, Khan, & Barbetti, 2016).…”
Section: Major Root Diseases Of Grain Legumesmentioning
confidence: 99%
“…Didymella pinodella or Phoma medicaginis var. pinodella ) and represent a threat to legume cultivations worldwide (Aveskamp, de Gruyter, Woudenberg, Verkley, & Crous, ; Baćanović‐Šišić, Šišić, Schmidt, & Finckh, ; Barilli, Cobos, & Rubiales, ; Haware, ; Tran, You, Khan, & Barbetti, ). These phytopathogenic fungi are responsible for severe leaf and stem spots and root rots on many legume host plants including pea, chickpea, lentil, and faba bean (Muehlbauer & Chen, ).…”
Section: Introductionmentioning
confidence: 99%
“…The alteration resulted in that the number of the pathogens which should have been a normal commensal increased. For the healthy group, the number of plant-pathogenic Didymella (Barilli et al, 2016; Ranjbar Sistani et al, 2017) and Filobasidium , presented a significant increase in the gut compared with the sick groups (Figure 6A,C,D). The healthy hepatopancreas group had a significantly higher abundance of Pyrenochaetopsis than the sick hepatopancreas groups (Figure 6B,E).…”
Section: Discussionmentioning
confidence: 99%